2014
DOI: 10.1515/chem-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Immunoactive ionic liquids based on 2-hydroxyethylamines and 1-R-indol-3-ylsulfanylacetic acids. Crystal and molecular structure of immunodepressant tris-(2-hydroxyethyl)ammonium indol-3-ylsulfanylacetate

Abstract: Abstract:Immunoactive ionic liquids (2-hydroxyethyl) ammonium 1-R-indol-3-ylsulfanyl-acetates HNwere synthesized by the reaction of (2-hydroxyethyl)amines with indol-3-ylsulfanylaceticor 1-benzylindol-3-ylsulfanylacetic acid. 1: R 1 = R 2 = CH 2 CH 2 OH, R 3 = H; 2: R 1 = СН 3 ,R 2 =CH 2 CH 2 OH, R 3 = H; 3: R 1 = R 2 = CH 3 , R 3 = H; 4: R 1 = R 2 = CH 2 CH 2 OH, R 3 = СH 2 С 6 Н 5 ; 5: R 1 = СН 3 ; R 2 = CH 2 CH 2 OH; R 3 = СH 2 С 6 Н 5 . The structure of each compound was elucidated by IR, NMR 1 H, 13 С, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…В данном контексте перспективны синтезированные нами доступные физиологически активные соединения -протатраны [5][6][7][8][9][10][11][12]. В качестве основы для дизайна протатранов выбраны два вида доступных реактивов (компонентов): биогенные этаноламины (в частности, триэтаноламин) и биологически активные арилхалькогенилуксусные кислоты.…”
Section: Introductionunclassified
“…В данном контексте перспективны синтезированные нами доступные физиологически активные соединения -протатраны [5][6][7][8][9][10][11][12]. В качестве основы для дизайна протатранов выбраны два вида доступных реактивов (компонентов): биогенные этаноламины (в частности, триэтаноламин) и биологически активные арилхалькогенилуксусные кислоты.…”
Section: Introductionunclassified
“…As a result of multi‐year research, we have synthesized about 300 atranes (silatranes, hydrometallatranes, protatranes, metallprotatranes, aroxyprotatranes and similar ionic complexes) from three pharmacophoric components, biogenic ethanolamines (and other amines), biologically active acids and essential metals …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the combination of two or more bioactive components in one molecule can ensure their synergistic effect . The compounds obtained are promising substances for agriculture, pharmacology, medicine, microbiology and biotechnology …”
Section: Introductionmentioning
confidence: 99%
“…In light of this, the chemical compounds synthesized at the Irkutsk institute of chemistry SB RAS can be considered as potential such materials. In particular, numerous tris-(2 hydroxyethyl) ammonium arylchalcogenylacetates, so-called “protatranes”, attract special interest [[17], [18], [19], [20]].…”
Section: Introductionmentioning
confidence: 99%
“…1), usually found as colourless low-melting powders or viscous protonic alkanolammonium ionic liquids (PAIL) [[24], [25], [26], [27], [28], [29]]. They are stable upon storage and highly soluble in water, alcohols, and other organic solvents [[17], [18], [19], [20],30].
Fig.
…”
Section: Introductionmentioning
confidence: 99%